Sound absorption calculation impedance method for resonator ceiling / Impedansinis rezonansinių kabamųjų lubų garso absorbcijos skaičiaytmo metodas - Stauskis, V. (Journal of Civil Engineering and Management, 1996)
The theoretical model of the suspended ceiling interspaced between the plane surfaces along and across the hall is analysed. The impedance method is used.A computer program has been developed to calculate, using the obtained formula, the sound absorption factors of the suspended interairspaced ceiling for the reading hall, the total absorption of this hall and the time of reverberation with varying width of the airspaces and their distance from the stiff plane surface. The obtained calculation results show the significant increase of the total hall absorption for the falling down wavre frequency. For a suitably selected width, number and distance from the stiff plane surface of the airspaces, it is possible to get the same acoustic absorption effect as for the special sound absorbing structures.Article in Lithuanian.First Published Online: 26 Jul 2012